Kolumbayeva S.Zh., Lovinskaya A.V., Abilev S.K., Voronova N. The Experimental Study Of The Mutagenic Action Of N-Nitrosodimethylamine In Mice: Al-Farabi Kazakh National University, Kazakhstan, Almaty; Vavilov Institute of General Genetics, Russian Academy of Sciences, Russia, Moscow (Eurasian Journal of Ecology, 2018)
The mutagenic activity of N-nitrosodimethylamine (NDMA) in the laboratory mice was studied usingthe chromosome aberration test. It was established that NDMA with intraperitoneal single administration(acute experience) in doses of 2.0; 4,0 and 8,0 mg/kg induced chromosomal aberrations in the mouse bonemarrow cells with a frequency statistically significantly exceeding the control level. With an increase in thedose of xenobiotics, the frequency of aberrant cells increased by 2.23 (p